Cheap chicken in Africa: Would import restrictions be pro-poor? - Isabel Knößlsdorfer; Matin Qaim (Food Security, 2023)
Europe's chicken exports to Africa have long been criticised for their negative effects on local producers. However, while cheap chicken imports may hurt African poultry farmers, the same cheap imports benefit African consumers and improve their access to affordable nutrients. A few African countries have established import restrictions, but it is unclear how such policies affect different population groups and whether the potential benefits for farmers outweigh the broader social costs. We use nationally representative household data from Ghana and a partial-equilibrium framework to simulate domestic household supply, consumption, and overall welfare effects of two hypothetical policies, namely a 50% import tariff on chicken and a complete import ban. Our results suggest that both policies would lead to increased domestic chicken prices with negative consumption effects that are much larger than the positive supply effects. Average poor and non-poor households in rural and urban areas would suffer welfare losses from these import restrictions. While many households purchase and consume chicken, relatively few produce chicken and only very few sell any chicken in the market. The findings imply that chicken import restrictions are not a pro-poor and welfare-enhancing policy. To compensate the few households particularly hurt by cheap chicken imports, targeted support measures would make more sense economically and socially than general import restrictions.
Keywords: 630; Trade policy; Armington assumption; Poverty; Welfare analysis; Chicken; Ghana